2010
DOI: 10.1890/08-2323.1
|View full text |Cite
|
Sign up to set email alerts
|

Widespread density‐dependent seedling mortality promotes species coexistence in a highly diverse Amazonian rain forest

Abstract: Negative density-dependent mortality can promote species coexistence through a spacing mechanism that prevents species from becoming too locally abundant. Negative density-dependent seedling mortality can be caused by interactions among seedlings or between seedlings and neighboring adults if the density of neighbors affects the strength of competition or facilitates the attack of natural enemies. We investigated the effects of seedling and adult neighborhoods on the survival of newly recruited seedlings for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
205
9
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(231 citation statements)
references
References 48 publications
14
205
9
3
Order By: Relevance
“…Ample evidence from tree communities around the world indicates that growth and survival are reduced when neighbors are of the same species (conspecifics) rather than different species (heterospecifics) (e.g., Hubbell 2009, Bai et al 2012). More recently, researchers have turned their focus to testing whether the phylogenetic relatedness of heterospecific neighbors also influences tree performance in natural communities, with mixed results (Webb et al 2006, Metz et al 2010 …”
Section: Introductionmentioning
confidence: 99%
“…Ample evidence from tree communities around the world indicates that growth and survival are reduced when neighbors are of the same species (conspecifics) rather than different species (heterospecifics) (e.g., Hubbell 2009, Bai et al 2012). More recently, researchers have turned their focus to testing whether the phylogenetic relatedness of heterospecific neighbors also influences tree performance in natural communities, with mixed results (Webb et al 2006, Metz et al 2010 …”
Section: Introductionmentioning
confidence: 99%
“…Despite these challenges, ecologists have made progress through analyzing long-term forest dynamics data sets (e.g., Condit et al 2006;Wills et al 2006;Swenson et al 2012b;Muscarella et al 2013). Recent studies have shown that nonrandom mortality is particularly high in the smallest size classes in tropical tree communities, and this leaves a disproportionally large imprint on patterns of coexistence through to adulthood (Bagchi et al 2010(Bagchi et al , 2014Metz et al 2010;Paine et al 2012;Green et al 2014). Uncovering the ecological mechanisms that determine the seed-to-seedling transition and their effects on tropical tree coexistence and community dynamics (Levine and Murell 2003) is an essential goal.…”
Section: Introductionmentioning
confidence: 99%
“…Seedling and sapling studies have argued for the importance of negative density dependence (Harms et al 2000;Metz et al 2010), abiotic filtering , or stochastic survivorship (Paine and Harms 2009). However, it is more likely that all of these factors act at the same time (e.g., Swenson and Enquist 2009), making it important to disentangle their importance in structuring tropical tree communities through space and time.…”
Section: Introductionmentioning
confidence: 99%
“…为脆弱、对生境变化最为敏感的时期 (Clark & Clark, 1984;Wright et al, 2005;Muller-Landau et al, 2008), 植物体在幼苗阶段具有较明显的时空变化 (李晓亮等, 2009; 张健等, 2009)。 因此探究导致群落 乔木幼苗动态变化的原因对于理解群落物种共存具 有重要意义 (Kelly & Bowler, 2002;Queenborough et al, 2007), 有助于我们了解和预测群落的组成、演 替过程, 以及进行合理的森林经营 (Wright et al, 2005;Muller-Landau et al, 2008)。 林下幼苗的更新过程是森林生态学研究的重要 内容, 近年来国内外学者做了大量研究, 其主要内 容包括: 1)幼苗的时空格局与动态 (Wright et al, 2005), 如Metz等(2008)分析了4块热带样地的幼苗 数据, 表明幼苗数量存在较大的时间和空间变异, 这些变异主要是由幼苗个体的新生和死亡所导致 的; 2)负密度制约理论和生态位理论等物种共存机 制假说的验证 (Canham et al, 2004;Muller-Landau et al, 2008;Comita & Engelbrecht, 2009;Queenborough et al, 2009;Metz et al, 2010;Metz, 2012;Oshima et al, 2015), 如Comita和Hubbell ( (Chen et al, 2010;Bai et al, 2012;Lin et al, 2014;肖翠等, 2015) ratios > 1 (95%的置信区间)表明是正相关; 而Odds. 图4 不同种子传播模式乔木幼苗存活最优模型各参数的优势比率, 圆圈表示各参数在模型中的估计值, 水平线表示95%的 置信区间, 显著的参数估计值用实心圆表示, 参数缩写见表2。 Fig.…”
Section: 在植物生活史中 幼苗阶段是植物个体生长最unclassified